2012
DOI: 10.1007/s00586-012-2400-2
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects, hemodynamic changes and cement leakage during multilevel cement balloon kyphoplasty

Abstract: Purpose The purpose of this study is to evaluate the effects of multilevel balloon kyphoplasty (BK) on blood pressure, blood gases and cement leakage. Methods This is a prospective study of 63 patients: 31 were treated for osteoporotic vertebral compressive fractures (OVCF) and 32 for osteolytic tumors (OT). Twentysix patients were treated at 1 level, 15 at 2, 2 at 3, 6 at 4, 3 at 5, 4 at 6, 5 at 7 and 2 at 8. PPMA was used in 43 patients and calcium phosphate in 20. All patients were treated under general ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
10
1
2
Order By: Relevance
“…It was possibly closely associated with vertebral endplate-disc injury in adjacent disc space and extrapedicular puncture for intervertebral space. The cement leakage ratio was similar to previous studies about cement augmentation for severe vertebrae fractures 23,24 . In our study, fortunately, the leakages were clinically asymptomatic.…”
Section: Discussionsupporting
confidence: 89%
“…It was possibly closely associated with vertebral endplate-disc injury in adjacent disc space and extrapedicular puncture for intervertebral space. The cement leakage ratio was similar to previous studies about cement augmentation for severe vertebrae fractures 23,24 . In our study, fortunately, the leakages were clinically asymptomatic.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies reckon that multilevel treatment in a single session has been shown to be feasible with no compromise of the technique's safety and efficacy and PVA is an efficient and safe technique for symptomatic vertebral fractures independently of the vertebrae number treated per session [15,16]. However, through multivariate linear regression analysis, we found in this study that the number of treated vertebrae is an important factor influencing the postoperative vertebral body height restoration.…”
Section: Influence Of the Number Of Treated Vertebrae On Postoperativmentioning
confidence: 36%
“…31 Some authors recommend performing these procedures with patients under local anesthesia to enable early detection of neurological compromise, 26 while others recommend general anesthesia for cardiorespiratory management, improved ability to obtain static images, and earlier intervention should clinically significant extravasation be suspected intraoperatively. 24 Obvious limitations of our review include the nature of the articles included, which represent relatively low levels of evidence. In many instances, case reports did not include all the information that we sought to extract.…”
Section: Discussionmentioning
confidence: 99%